Hip‐Hop Early Literacy in K–1 Classrooms. (22nd April 2019) - Meacham, Shuaib James; Meacham, Sohyun; Thompson, Misty; Graves, Hattie
Abstract: The authors employ hip‐hop music as a literacy heuristic aimed at supporting the literacy development of kindergarten and first‐grade students. How do young students learn to write hip‐hop lyrics? How do young students engage in hip‐hop reading and writing processes? The classroom examples show that students engaged in individual and interactive writing practices and a variety of practices associated with music disciplinary literacy. Hip‐hop reading and lyric composition constituted culturally relevant literacy, which connected the students to the literacy practices found in their community and families.